A comprehensive next generation sequencing tissue assay for Asian-prevalent cancers—Analytical validation and performance evaluation with clinical samples - Ng, Cedric Chuan-Young; Lim, Sandy; Lim, Abner Herbert; Md Nasir, Nur Diyana; Zhang, Jingxian; Rajasegaran, Vikneswari; Lee, Jing Yi; Kok, Jessica Sook Ting; Thike, Aye Aye; Lim, Johnathan Xiande; Weng, Ruifen; Yee, Sidney; et al. (Frontiers in Molecular Biosciences, 2022)
Introduction: A well-validated diagnostic assay with curated biomarkers complements clinicopathological factors to facilitate early diagnosis and ensure timely treatment delivery. This study focuses on an Asian-centric cancer diagnostic assay designed and thoroughly validated against commercially available standard references and a cohort of over 200 clinical specimens spanning 12 diverse Asian-centric cancer types. Methods: The assay uses hybrid-capture probes capable of profiling DNA aberrations from 572 cancer-related genes and 91 RNA fusion partners. The panel can detect clinically-tractable biomarkers such as microsatellite instability (MSI) and tumor mutation burden (TMB). Results: Analytical evaluation demonstrated 100% specificity and 99.9% sensitivity within a ≥5% VAF limit of detection (LoD) for SNV/Indels. RNA-based fusion features an LoD of ≥5 copies per nanogram input when evaluated against commercial references. Excellent linearity and concordance were observed when benchmarking against orthogonal methods in identifying MSI status, TMB scores and RNA fusions. Actionable genetic alterations were identified in 65% of the clinical samples. Conclusion: These results demonstrate a molecular diagnostic assay that accurately detects genomic alterations and complex biomarkers. The data also supports an excellent performance of this assay for making critical diagnoses and well-informed therapeutic decisions in Asian prevalent cancers.